Intrapartum Fetal Monitoring: Pathophysiology and Evolution of Various Techniques - Godinho, Myron; De, Somsubhra (Journal of Asian Scientific Research, 2018)
Perinatal hypoxia has been a source of major concern for the pregnant woman and her obstetrician alike. The former was plagued by constant worries of neonatal morbidity and mortality and the latter, by constant threat of medical litigations. Intrapartum fetal monitoring (IPFM) played an important role in the attempt to establish equilibrium. Initially, intermittent auscultation was the only method of monitoring the well-being of fetus during labor. Further research led to the evolution of electronic fetal monitoring, scalp blood sampling, fetal pulse oximetry, ST-analysis of the fetal ECG and the use of sophisticated magnetism and infra-red optics. A trial using artificial intelligence in IPFM has recently reached its final phase. Even as more novel methods of monitoring continue to emerge, the perfect monitoring technique still remains to be discovered. Analysis made it evident that no single method was capable of distinguishing true cases of fetal distress from false one, sufficiently accurately. A combination of two or more methods is required for a reliable diagnosis to be obtained, and current treatment protocols should reflect this. The concurrent use of two or more monitoring methods in an algorithmic manner will go a long way in reducing the incidence of perinatal morbidity especially in high risk obstetric cases.